A study of the double Laplace transform - Gupta, K. C. (Rev. Téc. Fac. Ing. Univ. Zulia)
In this paper, we first establish three new theorems concerning two-dimensional Laplace transform.Â Next, we obtain an interesting and general integral from an application of the first theorem.